Estimación de los campos electromagnéticos del tramo perteneciente a la provincia de Cotopaxi de la línea santa Rosa-Totoras 230 kv - Velasco Cayo, María Fernanda (2021)
Power system equipment when handling high voltage and current levels, are prone to generate electric and magnetic fields (EMF). Transmission lines, being part of the SEP and being at a low frequency (50/60Hz), generate an electric field when the conductor cables are subjected to a certain voltage, and a magnetic field when an electric current flow through them; these emission levels must be below the limits established by national and international regulations. The objective of this project is to estimate the EMF of the section belonging to the Cotopaxi Province of the Santa Rosa-Totoras 230 kV Line, for which, first, the state of the artworks associated with the study of the electric field, magnetic field, and EMF in electric power systems was reviewed. Then, the route of the transmission line was designed by means of the PLS_CADD software, and by means of the EMF calculation module of this program, the values of electric and magnetic fields of the transmission line were obtained. In addition, applying the calculation methodology used by the Electric Power Research Institute (EPRI), the levels of electric and magnetic fields emitted by the line under study were determined. Finally, with these results, a statistical analysis is performed to determine if the EMF emissions of the Santa Rosa-Totoras line are within the limits established by the International Commission on Non-Ionizing Radiation Protection (ICNIRP), as well as the most representative values of electric and magnetic field present within the easement strip.